Regulating the molar fraction of 4-hydroxybutyrate in Poly(3-hydroxybutyrate-co-4-hydroxybutyrate) by biological fermentation and enzymatic degradation - Ansari, Nor Faezah; Amirul, Al-Ashraf Abdullah (Springer Verlag, 2011)
The regulation of 4-hydroxybutyrate (4HB) molar fraction in the poly(3-hydroxybutyrate-co-4-hydroxybutyrate) [P(3HB-co-4HB)] of a local isolate Cupriavidus sp. USMAA1020 was attempted by employing a feeding strategy through fed-batch fermentation in 100-L fermenter. The growth of Cupriavidus sp. USMAA1020 was enhanced by frequently feeding carbon and nitrogen at a ratio of 5 (C/N 5) using a DO-stat with cascade mode at 20% (v/v) dissolved oxygen (DO). The feeding of C/N 5 and the use of the DOstat mode were able to regulate the 4HB composition from 0–67 mol% by sequential feeding of c-butyrolactone and supplementing oleic acid. A high 4HB molar fraction of 67 mol% with a PHA concentration of 5.2 g/L was successfully obtained by employing this feeding strategy. Notably, enzymatic degradation carried out enhanced the 4HB composition of the copolymer synthesized. PHB depolymerase enzyme from Acidovorax sp. was used to degrade this P(3HB-co-70-mol%4HB) copolymer and the 4HB composition could be increased up to 83 mol%. The degradation process was observed by monitoring the timedependent change in the weight loss of copolymer films. The percentage of weight loss of solvent-cast film increased proportionally up to 19% within 3 h, whereas salt-leached films showed 90% of weight loss within 3 h of incubation and were completely degraded by 4 h. The molecular weight (Mn) of the films treated with enzyme demonstrated a slight decrease. SEM observation exhibited a rough surface morphology of the copolymer degraded with depolymerase enzyme.